Pemanfaatan Citra Satelit Resolusi Tinggi pada Google Earth Pro dan SIG untuk Deteksi Kerusakan Infrastruktur Jalan dan Bangunan Akibat dari Abrasi di Pantai Pebuahan, Desa Banyubiru - Bagus Arya Yoga Bharata, Ida; Atmaja, Dewa Made; Gunamantha, I Made; Christiawan, Putu Indra; Setiabudi, Gede Iwan (Universitas Pendidikan Ganesha, 2025)
The coastal environment in some parts of Indonesia's coast is vulnerable to coastal dynamics, one of which is abrasion which threatens the organization at Pebuahan Beach, Banyubiru Village, Negara, Jembrana, Bali Island. The objectives of this research are 1) detecting environmental damage to road infrastructure and buildings resulting from abrasion at Pebuahan Beach, and 2) mapping environmental damage to road infrastructure and buildings resulting from abrasion at Pebuahan Beach. The research carried out was exploratory descriptive research using CSRT data available on Google Earth Pro at 3 different times, namely 2009, 2016, and 2023, which were collected through visual interpretation and digitization on the screen and then analyzed using a spatial approach. The research results showed that 184 buildings were washed away and 28 buildings were damaged during the 2009-2023 period. The percentage of buildings that were washed away and damaged was a total of 30% of buildings affected by abrasion during the 2009-2023 period. Apart from that, damage to road infrastructure covering 675.57 meters was washed away and 268.31 meters was damaged, or if combined, it reached 25% of the existing roads in the Pebuahan Beach residential area during the 2009-2023 period. The continuing damage that occurs makes it necessary to take concrete steps to address the large number of buildings and infrastructure that have been lost.